Development of a Growth Mindset-Based Coaching Supervision Model to Enhance Motivation and Academic Innovation Among Senior High School Teachers - Destha Purwa Nufusila; Sitti Hartinah; Khusnul Khotimah (Journal of Educational Sciences, 2026)
Teachers’ low levels of motivation and innovation in teaching stem from the lack of implementation of growth mindset-based coaching supervision. The purpose of this study is to develop a growth mindset-based coaching supervision model guide. This study employed the Research and Development (R&D) method by adapting the ADDIE model, which was limited to three stages: Analysis, Design, and Development (ADD).   The results showed that the growth mindset-based coaching supervision guide was deemed highly feasible based on an 88% expert validation rate. The limited pilot test yielded an average score of 89.2% in the “highly practical” category. Expert validation included an assessment of structure, content, clarity of instructions, and the model’s alignment with teachers’ needs at the school. The researcher utilized content validators, media/design validators, and language validators. The conclusion of this study is that the growth mindset-based coaching supervision guide is feasible and practical for use as an alternative solution to enhance the motivation and innovation of high school teachers at partner schools. This study provides a practical contribution to school principals in continuously developing teachers’ professional competencies through a humanistic, collaborative, and potential-oriented supervision approach.